ANALISIS DEVIASI KEMAJUAN PEKERJAAN BERDASARKAN PERSENTASE DURASI WAKTU PADA PEKERJAAN KONSTRUKSI BANGUNAN - aman, Mardi (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2023)
No construction work has the same progress—various factors as the cause of inequality. A positive progress deviation indicates good construction work. Otherwise, it is said to be bad if it has a negative value. The uncertain nature of the construction work causes 3 (three) possible scenarios of the value of the deviation of progress so that the three values ​​form one value of the deviation of the expected progress. Deviations of value greater than 10% for a duration from 0 to 70% are categorized as binding contracts. This study aims to determine the deviation of the progress of 25 construction works. The research method was quantitative. Data collection was carried out on 25 construction works that had been carried out. Data was taken from contractors directly. The results of the data analysis show that when 25%D is obtained, 10 poor-performing construction jobs, Next for 30%D construction work. 50%D and 70%D underperformed 9, respectively; 9; and 8. The largest positive progress deviation value is 15,362 at S70%D. The expected value of the largest progress deviation is positive 1.763. By knowing the value of negative progress expectations, contractors should control delays before the contract is completed.